Pengaruh carbon black pada pembuatan plastik untuk irigasi sistem tetes - Arum Yuniari; Dwi Wahini Nurhajati; Niken Karsiati (Majalah Kulit, Karet, dan Plastik, 2001)
The objective of this experiment was to know the influence carbon black was added to the plastics for drip irrigation systems. Plastics of 0,2 mm thickness for drip irrigation system was made from mixing of lwo density polyethylene (LDPE), high density polyethylene (HDPE) and carbon black by a blown film machine on the fixed processing condition. The investigated carbon black content were 0; 2,5; 5; 7,5; and 10 phr respectively and LDPE/HDPE ratio were 0/100, 50/50, 100/0 respectively. The physical properties tes showe and increasing of carbon black decreasing tensile strength, elongation at break, tear strength and brittleness. The best formulation was consist of HDPE 100 phr and carbon black 10 phr, with the physical properties as follows : tensile strength 158 kg/cm2, elongation at break 140%, and tear strength 91,46 kg/cm2.INTISARIPenelitian ini bertujuan untuk mengetahui pengaruh carbon black pada pembuatan plastic untuk irigasi system tetes. Plastic tebal 2 mm dibuat dari low density polyethylene (LDPE), high density polyethyln (HDPE) dan carbon black menggunakan mesin blown film pada kondisi proses yang tetap. Carbon black yang digunakan adalah 0; 2,5; 5; 7,5; 10 phr dan ratio LDPE/HDPE adalah 0/100, 50/50, 100/0 phr. Sifat fisis menunjukkan bahwa kenaikan carbon black menurunkan kuat tarik, kemuluran, kuat sobek dan kerapuhan. Formulasi terbaik terdiri dari HDPE 100 phr dan carbon black 10 phr, dengan sifat fisis sebagai berikut : kuat tarik 158 kg/cm2, kemuluran 140% dan kuat sobek 91,46 kg/cm2.